Compilation of Islamic Law within the Framework of State Typology: A Critical Analysis of the Reform of Islamic Family Law in Indonesia - Muslih, Muslih; Jera, Almi (ADHKI: JOURNAL OF ISLAMIC FAMILY LAW, 2024)
Objective: This article analyzes the Islamic Law Compilation (KHI) as a manifestation of state engagement with Islamic law, utilizing a state typology framework for analysis. Methods: Employing both doctrinal and socio-legal methodologies, the research elucidates how the political-religious dynamics in Indonesia influence the codification and reform of Islamic family law. Results: The study illustrates that Indonesia occupies a unique position among Muslim-majority nations, embodying a synthesis of secular regulation and religious accommodation. Three key findings emerge from this analysis: (1) the KHI occupies an ambiguous status within Indonesia's legal hierarchy, which constrains its enforcement capabilities; (2) recent rulings from the Constitutional Court have redirected the trajectory of Islamic family law reform, frequently circumventing formal legislative procedures; and (3) a more adaptive approach to reforming Islamic family law necessitates a methodological transition from a textual-normative interpretation to a contextual-substantive interpretation. Conclusion: The article concludes that future reforms in Islamic family law in Indonesia must strike a balance among religious values, constitutional principles, international human rights standards, and local wisdom to ensure sociological legitimacy while striving for legal certainty and justice.